Expression of VP1 gene as a DNA vaccine candidate for foot and mouth disease using phospholipid and poly-lactic acid nanoparticles as a delivery system - Wibowo Natalia; Siahu Celine; Gustari Sri; Kusumawati Asmarani (BIO Web of Conferences)
The Foot and Mouth Disease outbreaks in Indonesia in 2022 give several disadvantages for livestock. The primary treatment of reproductive pathologies involves a combination of prevention, diagnosis, and treatment. Prevention strategies include vaccination against specific diseases that cause reproductive disorders. Vaccination is the primary preventive measure in managing the spread of the FMD virus. The Viral Protein 1 (VP1) gene encodes the FMD virus capsid protein, which could be a target in developing a DNA vaccine for FMD. Therefore, the development of DNA vaccine in this study is focused on increasing VP1 gene expression using the pEGFP-N1 vector in HeLa cells as a mammalian cell model, using Lipofectamine as phospholipid nanoparticle and Poly-Lactate Acid (PLA) as polymer nanoparticle to increase delivery efficiency to target cells. The method used in this study is divided into three main stages, namely cloning and transformation of Plasmid DNA (pEGFP-N1-VP1) in competent E. coli DH5α cells; formulation of recombinant Plasmid DNA complexes of PLA nanoparticles and Lipofectamine Plasmid DNA nanoparticles; and determination of VP1 gene expression in a mammalian expression system. The VP1 gene delivered with Lipofectamine was successfully expressed at a level of 516.25-fold, while PLA was expressed at 114.08-fold in HeLa cells as a mammalian model. Both nanoparticles successfully delivered the VP1 gene into mammalian cells; however, the formulation of PLA nanoparticles requires further optimization to achieve more optimal results.